Potential Use of Invigoration Techniques to Improve Viability and Vigor of Soybean Seeds - Kusman, Hardi; Sudharmawan, A. A. K.; Fauzi, M. Taufik (Jurnal Biologi Tropis, 2025)
Demand for soybeans in Indonesia continues to increase along with population growth, but productivity remains low and dependent on imports. One of the key factors affecting soybean productivity is seed quality, which often deteriorates during storage. Seed invigoration, which includes techniques such as hydration-dehydration, hydropriming, and osmopriming, is a possible solution to improve soybean seed viability and vigor. This research used the literature survey method to collect and analyze data from various scientific sources. The results show that seed invigoration can improve the quality of soybean seeds by improving the germination process, increasing vigor, and optimizing water uptake. These techniques are especially important when seeds are sown in non-ideal conditions, such as arid or high salinity areas. Thus, the application of invigoration techniques has the potential to be an effective strategy for increasing soybean productivity in Indonesia and reducing import dependence.